General system of ( A,η) -maximal relaxed monotone variational inclusion problems based on generalized hybrid algorithms - Agarwal, Ravi P.; Verma, Ram U. (Communications in nonlinear science & numerical simulation, 2010)
In this paper, a new system of nonlinear (set-valued) variational inclusions involving ( A,η) -maximal relaxed monotone and relative ( A,η) -maximal monotone mappings in Hilbert spaces is introduced and its approximation solvability is examined. The notion of ( A,η) -maximal relaxed monotonicity generalizes the notion of general η-maximal monotonicity, including ( H,η) -maximal monotonicity (also referred to as ( H,η) -monotonicity in literature). Using the general ( A,η) -resolvent operator method, approximation solvability of this system based on a generalized hybrid iterative algorithm is investigated. Furthermore, for the nonlinear variational inclusion system on hand, corresponding nonlinear Yosida regularization inclusion system and nonlinear Yosida approximations are introduced, and as a result, it turns out that the solution set for the nonlinear variational inclusion system coincides with that of the corresponding Yosida regularization inclusion system. Approximation solvability of the Yosida regularization inclusion system is based on an existence theorem and related Yosida approximations. The obtained results are general in nature.